Encapsulation of Lactobacillus casei 01 by alginate along with hi-maize starch for exposure to a simulated gut model - Pankasemsuk T. (2017)
© 2016 A study of entrapped Lactobacillus casei 01 with 2% alginate along with 0.5–2% hi-maize starch by emulsion technique was conducted. The efficacy of this encapsulation was then carefully assessed by SEM microstructure as well as cell survivability in gastric, bile and colon fluids (simulated gut model). The results showed that alginate bead incorporating 1% hi-maize starch enabled optimal D value of viable cells in both gastric and bile fluids. In addition, the SEM images showed that these coating materials gave rise to more compact bacterial cells residing in the beads than applying alginate alone. In the colon experiment, coated Lactobacillus casei 01 had great influence on the augmentation of indigenous lactobacilli during 24 h fermentation, while the synthesized products of colon microbiome such as acetate, propionate and butyrate were progressively increased up to 48 h fermentation. However, these circumstances subsided upon prolonged fermentation due to the accumulation of dead cells and harmful substances to the cells.